Lateral magnetic tunnel junctions with a heterointerface‐induced half‐metallic electrode. (August 2022) - Song, Yanxing; Chai, Changchun; Fan, Qingyang; Zhang, Wei; Yang, Yintang
Abstract: The electronic properties of monolayer MnGeSe3 and MnGeSe3 /CrI3 heterostructures were investigated by density functional theory (DFT) calculations. In the MnGeSe3 /CrI3 heterostructure, the half-metal MnGeSe3 can induce the half-metallic properties of CrI3 by charge transfer. Based on the charge transfer effect, we designed lateral magnetic tunnel junctions (MTJs) in which MnGeSe3 attaches to the bottom of the detached CrI3 crystals. This model can form half-metallic-CrI3 /insulating-CrI3 /half-metallic-CrI3 MTJs, thereby avoiding the loss of half-metallic properties caused by defects and lattice distortion at the interface of traditional half-metallic MTJs. According to the extension length of the CrI3 layer, they can be divided into heteroelectrode MTJs and MnGeSe3 -electrode MTJs. Half-metallic electrode MTJs are famous for their ultrahigh tunnel magnetoresistance (TMR), and the ability to maintain a stable TMR under bias has become the other significant target of half-metal MTJs. We find that the half-metallic gap of the electrode material can affect the threshold bias voltage in antiparallel configuration (APC) when opening and closing. The larger the half-metallic gap is, the larger the bias voltage required to generate the tunneling current, and correspondingly, the better its ability to maintain a high TMR. Therefore, it is imperative to find two-dimensional half-metallic materials with large half-metallic gaps. Our results provide a new idea for designing half-metallic electrode MTJs and provide a new understanding of the mechanism of half-metallic electrode MTJs under bias. Graphical abstract: Image 1 Highlights: CrI3 can obtain half-metallic properties through charge transfer in MnGeSe3 /CrI3 heterojunction. The lateral MTJs with a heterointerface-induced half-metallic electrode were firstly proposed. Ultra high TMR ratios are found in metallic-electrode MTJs. In APC, half-metallic gap of the electrode has significant effect on the threshold bias voltage when opening and closing.